Actionable postcolonial theory in education - Andreotti, Vanessa (Postcolonial studies in education, 2011)
"This book illustrates how postcolonial theory can be put to work in education. It offers an accessible and handy overview and comparison of postcolonial theory and other theoretical debates related to critiques of Western ethnocentrism and hegemony. It also offers examples that illustrate how a discursive strand of postcolonial theory has been applied successfully in the contexts of educational research/critique and in pioneering pedagogical projects. This book supports educators and researchers in education to engage with postcolonial theoretical frameworks and their implications for research and educational practice"